2022
DOI: 10.1021/acs.macromol.2c01596
|View full text |Cite
|
Sign up to set email alerts
|

Rational Optimization of Bifunctional Organoboron Catalysts for Versatile Polyethers via Ring-Opening Polymerization of Epoxides

Abstract: Quaternary ammonium and phosphonium borane bifunctional catalysts have shown high catalytic performance in ring-opening polymerization (ROP) of epoxides to produce polyether. Herein, we systematically investigate a series of well-defined organoboron catalysts by varying the electronic and steric properties of the Lewis acidic boron (B) centers, manipulating the steric hindrance on the ammonium cation (N+), adjusting the distance between B and N+, and regulating the nucleic B number of the catalysts. The invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 43 publications
3
32
0
5
Order By: Relevance
“…Coherently, computational studies have shown that the energy barrier for adopting an ideal conformation is lowered by a high steric demand around the nitrogen atom. 154 Finally, in accordance with previous results, it was confirmed that catalyst activity multiplies with the number of boron groups, that is tri- and tetranuclear structures outperformed the dinuclear ones.…”
Section: Modified Boranessupporting
confidence: 89%
See 2 more Smart Citations
“…Coherently, computational studies have shown that the energy barrier for adopting an ideal conformation is lowered by a high steric demand around the nitrogen atom. 154 Finally, in accordance with previous results, it was confirmed that catalyst activity multiplies with the number of boron groups, that is tri- and tetranuclear structures outperformed the dinuclear ones.…”
Section: Modified Boranessupporting
confidence: 89%
“…A systematic variation of L = 3, 4, 5 and 6 revealed a stepwise decrease of activity in this order, with an observed TOF of 585 h −1 , 380 h −1 , 325 h −1 and 113 h −1 . 154 A very comparable trend was also found for EO monomer (TOF = 24 600 h −1 , 16 150 h −1 , 12 900 h −1 and 7750 h −1 , respectively). Thus, gradually activity of the dinuclear catalysts decreases as the linker length increases.…”
Section: Polymer Chemistry Reviewsupporting
confidence: 65%
See 1 more Smart Citation
“…The produced PCPC can be recycled to the pristine CPO in 99% NMR yield and 95% isolated yield. A combination pathway of random chain scission and chain unzipping the depolymerization of PCPC was provided [131–136] …”
Section: Chemically Recyclable Aliphatic Carbonatesmentioning
confidence: 99%
“…A combination pathway of random chain scission and chain unzipping the depolymerization of PCPC was provided. [131][132][133][134][135][136] 1,4-cyclohexadiene extracted from renewable vegetable oils (e. g. linoleic acid) is oxidized by mCPBA or oxycodone to produce 1,4-cyclohexadiene oxide (1,. This epoxide can be hydrogenated to obtain cyclohexene oxide (CHO), which can be selectively copolymerized with CO 2 to produce polycyclohexene carbonate (PCHC) in the presence of a metal Zn catalyst in toluene under 8 atm CO 2 pressure at room temperature.…”
Section: Co 2 and Epoxides Copolymermentioning
confidence: 99%